Making China modern from the Great Qing to Xi Jinping - Mühlhahn, Klaus 1963- (Harvard University Press, 2019)
Cover -- Title Page -- Copyright -- Dedication -- Epigraph -- Contents -- Timeline: China, 1644-2017 -- List of Maps -- Introduction -- Part 1. The Rise and Fall of Qing China -- 1. Age of Glory: 1644-1800 -- 2. Reordering the Chinese World: 1800-1870 -- 3. Late Qing Predicaments: 1870-1900 -- Part 2. Chinese Revolutions -- 4. Upending the Empire: 1900-1919 -- 5. Rebuilding during the Republican Era: 1920-1937 -- 6. China at War: 1937-1948 -- Part 3. Remaking China -- 7. Socialist Transformation: 1949-1955 -- 8. Leaping Ahead: 1955-1960 -- 9. Overthrowing Everything: 1961-1976 -- Part 4. China Rising -- 10. Reform and Opening: 1977-1989 -- 11. Overall Advance: 1990-2012 -- 12. Ambitions and Anxieties: Contemporary China -- Abbreviations -- Notes -- Acknowledgments -- Index